Analysis Of Physical Fitness Level Of Class VIII Students Of SMP Negeri 17 Krui - Saputra, Julian; Ariesna , Rachmat Dody; Bela, Yohana (Social Sciences Journal, 2024)
The problem in this research is the low level of physical fitness of the students of Clas VII SMP Negeri 17 Krui. The purpose of this study was to determine how the level of physical fitness of the students of Clas VII SMP Negeri 17 Krui.This type of research is descriptive. The population in this study were all students of Clas VII SMP Negeri 17 Krui. While the sample amounted to 40 people with a sampling technique that is proportionate stratified random sampling technique. The research instrument uses an Indonesian physical fitness test measuring instrument. The data analysis technique used descriptive percentage analysis.Based on the results of the study, it was found that the level of physical fitness of the students of Clas VII SMP Negeri 17 Krui was in the less detailed category, namely; 1) running 50 meters is in the moderate category. 2) Lifting the body hanging / hanging elbow bends are in the less category. 3) lie down for 60 seconds in the good category. 4) vertical jump is in the less category. 5) running 1000/800 meters is in the less category .